“It is a false safety net”: A qualitative exploration of multiprofessional staff experiences of insulin management in hospitalised older or frail adults with diabetes undergoing surgery - Christina Lange Ferreira; Hellena Habte-Asres; Angus Forbes; Kirsty Winkley (PLoS ONE, 2025)
Aim To explore multiprofessional hospital staff’s experiences and perspectives of insulin use and safety review in older or frail adults with diabetes undergoing surgery. Method Twenty-three semi-structured interviews amongst multiprofessional staff supporting four surgical wards (elective and emergency) at a single NHS Trust in a rural county in England. Interviews were recorded, transcribed and analysed using framework analysis approach. Results Six main themes identified: (1) Transitioning through care: Misalignments across insulin related interacting components contribute to insulin errors (2) Coping with complexity, changes and ambiguity; at clinical, operational and organisational levels (3) Staff knowledge and confidence gaps affect insulin safety (4) Fostering patient empowerment; patient empowerment can be hindered by staff assumptions and inflexibility of hospital environment (5) Staff support systems; communication, power dynamics influence insulin safety (6) System learning as a cultural challenge; absence of systems approach and reactive to harm. Conclusion This study provides valuable insights into reported complexities of managing insulin-related interacting components during surgical admission. Findings could inform how managers, leaders and organisations approach and consider multiple components implicated in safe hospital insulin use to build system resilience. Future research can build on insights from this study to develop interventions supporting system-based approaches to hospital insulin safety.